SUGGESTIONS AND WAYS TO SEIZE THE ESL ADVANTAGE AND COMPENSATE FOR THE LACK OF READY COMMUNICATIVE SITUATIONS OUTSIDE THE EFL CLASSROOMS IN INDONESIA - Sutaryo Sutaryo; Nurprihatina Hasan (FKIP Universitas Khairun, 2020)
This article discusses some suggestion and ways to seize the English as a second language (ESL) advantages and compensate for the lack of ready communicative situations outside the English as a foreign language (EFL) classrooms such as in Indonesia to maximize English language learning. This is particularly for lecturers or teachers who play a very important role in facilitating any opportunity for their students to use English in real communicative context in English as a foreign language (EFL) context.